2015
DOI: 10.1532/hsf.1228
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Congenital Heart Disease Associated Pulmonary Hypertension

Abstract: Preoperative inflammation markers may be correlated with the progression of pulmonary hypertensive disease, but further studies with larger sample size are needed to determine the predictive role of these markers for postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
7
1
1
Order By: Relevance
“…This can be explained by the fact that our study was lack of mortality, which was estimated to develop at higher pNLRs as in adult cohorts. [3][4][5] In contrary to Gürsoy et al, [8] although the pNLR in the current series was approximate to the Gürsoy et al's cohort, it was probably not high enough for the development of morbidity in our cohort. This circumstance may be a reflection of the retrospective design of the study and extensive implementation of the exclusion criteria leading to a sterile patient cohort in which 142 patients with predisposing risk factors for morbidity were excluded.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…This can be explained by the fact that our study was lack of mortality, which was estimated to develop at higher pNLRs as in adult cohorts. [3][4][5] In contrary to Gürsoy et al, [8] although the pNLR in the current series was approximate to the Gürsoy et al's cohort, it was probably not high enough for the development of morbidity in our cohort. This circumstance may be a reflection of the retrospective design of the study and extensive implementation of the exclusion criteria leading to a sterile patient cohort in which 142 patients with predisposing risk factors for morbidity were excluded.…”
Section: Discussioncontrasting
confidence: 97%
“…[1,2] The pNLR has been investigated in cardiovascular diseases in search of a powerful predictor of outcome. [3][4][5][6][7][8] However, as the pNLR has not been extensively evaluated in cyanotic pediatric cardiac surgery cases, we investigated whether the pNLR could predict postoperative morbidity in TOF in whom complete repair was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated levels of CRP can be used to distinguish individuals with increased cardiovascular morbidity and mortality among apparently healthy subjects, patients with coronary artery disease, or those with atherosclerosis (19)(20)(21). It was found that serum concentrations of highly sensitive CRP positively correlated with pulmonary artery pressures in children with cystic fibrosis (22).…”
Section: Discussionmentioning
confidence: 99%